In-Use Stability Sediaan Injeksi Hidrokortison di Rumah Sakit Rujukan Daerah Jawa Tengah - Genatrika, Erza; Sundhani, Elza; Fitri, Adriana Eka (Jurnal Ilmiah Medicamento, 2025)
Hydrocortisone Sodium Succinate 50mg injection is widely used in perinatology wards. These wards cater to newborns (0-28 days), low birth weight (<2.5 kg), or premature babies (<37 weeks), requiring special handling. The use of this injection requires a very small dose, so one vial of hydrocortisone injection can be used for more than one patient. Therefore, the remainder of this hydrocortisone injection is often stored for 24 hours in the refrigerator which will later be reused on other patients. This study aims to determine the in-use stability of hydrocortisone injection stored for 24 hours at 4oC and 25oC. This is certainly to improve patient safety. The data collection technique uses an observational method on hydrocortisone injection samples with 3 replications. In-use stability is assessed from the results of organoleptic tests, pH tests, viscosity tests, determination of drug levels using UV-VIS spectrophotometry and sterility tests. Testing was conducted on days 0, 1, 2, 3, 7, 14 and 30. The results of the study showed that hydrocortisone injection preparations stored for 1 day at 4°C or 25°C in the perinatology ward were no longer physicochemically stable (concentration). Chemical degradation began on day 1, then microbial contamination occurred immediately after completion of compounding in the ward (day 0). This is because reconstitution was not carried out in a clean room in accordance with USP <797>. It can be concluded that hydrocortisone injection preparations prepared in this hospital are not recommended for administration to patients after 1 day of storage and must be compounded in a clean room.